Blood Biochemical Profile, Growth Performance, Carcass Characteristics and Meat Quality of Mallard and Muscovy Ducks Fed Diet Supplemented with Bay Leaves (Syzygium polyanthum) - Ismoyowati; Indrasanti, Diana; Sumarmono, Juni (International Journal of Poultry Science, 2015)
The purpose of this experiment was to investigate the interaction effect between genetic and bay leaf supplementation in the diet on blood biochemical profile, growth performance, carcass characteristics and meat quality of local Mallard and Muscovy ducks. A total of 128 (64 of each breed) day old male ducks were utilized for the study. The experimental design was completely randomized in a factorial pattern. The first factor was breed of duck (Mallard and Muscovy) and the second factor was bay leaf supplementation in the diet at various levels (0%-control, 3, 6 and 9%. The breed type had highly significant (p